Evaluation of Reproductive Outcome in Infertile Hypothyroid Women on Thyroxine Therapy - Leena Wadhwa; K Monica Marghret; Sarika Arora (Wolters Kluwer Medknow Publications, 2020)
Introduction: Thyroid dysfunction is associated with increased risk of infertility. Serum thyroid stimulating hormone (TSH) screening in all women seeking infertility care is recommended and hypothyroid infertile women should be treated with thyroxine until the preconception serum TSH level is <2.5 mU/l.[1] However, insufficient evidence exist to determine if thyroxine therapy improves fertility in subclinical hypothyroid women who are trying to conceive naturally. Objectives: The objective is to study the effect of thyroxine therapy on reproductive outcome in infertile women with clinical and subclinical hypothyroidism (SCH). Materials and Methods: The study is a descriptive cohort study with 72 subjects. Women between 20 and 40 years of age with primary or secondary infertility with hypothyroidism were studied and thyroid profile including free T3, T4, TSH, and thyroid antibodies were done. Thyroxine was given to clinical, subclinical hypothyroid subjects depending on TSH levels such that serum TSH levels are maintained < 2.5 mU/L. Serial thyroid function test was done every 6 weeks until the optimal levels were reached. Once normal TSH levels were reached subjects were followed up for 6 months. Reproductive outcome was analyzed in two groups. Group A included hypothyroid infertile women who conceived and Group B included those who did not conceive following thyroxine therapy. Results: Thirty-eight out of 72 subjects (54%) conceived during thyroxine treatment (Group A) of which 4 cases had miscarriage. Maximum infertile women in Group A (20/38) conceived between 6 and 12 months (52.6%) of thyroxine therapy. Significant decrease was observed in mean TSH levels over a period of 6 months (P < 0.001). The infertility period until pregnancy in Group A reduced significantly from 5.2 ± 1.8 years to 0.5 ± 0.8 years after thyroxine treatment (P = 0.001). Conclusion: Thyroxine therapy enhances fertility in infertile women with clinical and SCH.